Relationship between measurement salt taste threshold and salt intake in japanese primary school students, parents and high school students using test papers of low concentration taste threshold: Relationship between salt intake and salt taste threshold - Sawai, Asuka; Nagata, Yuki; Kudo, Fumiyo; Fujii, Hitoshi; Sawai, Shinya; Fujikawa, Tetsuya (Progress in Nutrition, 2022)
AIM: Because of the inspection of salty taste has a background developed mainly for extraction of taste disorders and the guidance on diet for patients,　the information in healthy young people isn’t detail. Recently, it reported that salt taste thresholds in university students using low concentration threshold test paper was about 60% as concentration as previously reports using taste paper.We used test papers of low concentration taste threshold  to investigate the salt taste threshold in school children, their parents, and in high school students.METHODS: The subjects comprised 26 families (26 fathers, 26 mothers, and their 26 children) and 25 female high school students. Salt intake per day was determined by measuring urinary salt excretion. Different concentrations of salt taste test papers (Salsave®) were used to evaluate the salt taste threshold.RESULTS: Mean salt intakes (g/day) were 7.32±1.63 (children), 7.83±2.30 (mothers), and 9.05±2.73 (fathers). Mean salt taste thresholds (mg/cm2) were 0.28±0.33 (children), 0.33±0.25 (mothers), and 0.25±0.14 (fathers). High school students’ mean salt intake was 8.52±3.00, and salt taste threshold was 0.28±0.13. Those salt taste threshold concentration were accuracy lower than that of previously reports. Also, significant positive correlations between recognized salt taste thresholds and salt intake were found in the children, boy’s fathers and high school students (P < 0.05).CONCLUSION: Using low concentration test papers which not for sale because of unprofitable previously, could analyze the salty taste threshold of healthy volunteers in detail. The results suggested a relationship between daily salt intake and the salt taste threshold.